Um modelo para formação de padrões em processos de erosão - deposição - Maionchi, Daniela de Oliveira (2008)
In this work, we study pattern formation through computer simulations. We propose a model that describes the erosion-deposition process in an one-layer system. We analyze the erosion process existing in nature from the microscopic point of view, what means that we consider a granular medium with well-defined spherical particles. A fluid flows through this system due to a gradient of pressure. We use the software FLUENT to determine the velocity profile and the flux of the fluid in network of capillaries created between the particles and hence, the permeability of each channel of the system. We consider that the only force acting on each particle is due to the fluid and is given by the Stokes Law. As the particles of the system are dislocated, we make two different considerations about interaction between them: in the first one, the friction between the grains is large and in the second one, the friction is null. As the system evolves in time, patterns obtained depend on the porosity considered. The patterns obtained with the first consideration are similiar to the patterns already obtained experimentally, while the formation of channels observed using the second one is consistent with that observed in a variety of natural phenomena.